Synthesis of Fused, Isolated and Spiro 1,24-triazinoindole Derivatives - Abdel-Rahman, R.M.; Fawzy, M.M. (Asian Journal of Chemistry, 2010)
The synthesis of fused, isolated and spiro 1,2,4-triazinoindole derivatives have been achieved by the reaction of isatin 3-thiosemicarbazone(I) and or 3-(cyano)-3-thiosemicarbazide(X) with chloroacetic acid and aromatic aldehydes in neutral or acidic medium. The structures of new the compounds have been confirmed from spectral and analytical data.